Impact of first trimester bleeding on feto-maternal outcome : A cohort study in a tertiary care hospital of Eastern India - Samrat Chakrabarti (Placentum)
OBJECTIVE: To evaluate the impact of first trimester bleeding on maternal and perinatal outcomes in pregnancies that crossed period of viability.BACKGROUND: Threatened miscarriage is presumed to be associated with adverse maternal and perinatal outcome which needs to be systematically evaluated and documentedMETHODS: A prospective cohort study having 100 participants where pregnancy outcomes were compared between 50 patients with threatened miscarriage [TM] and 50 uncomplicated controls. Baseline demographic and clinical history were recorded to make the two arms comparable. Maternal outcomes in terms of antepartum haemorrhage [APH], preeclampsia, preterm labour, operative morbidity due to caesarean section and neonatal outcomes including low birth weight (LBW), prematurity and perinatal death were compared among case and control groups.RESULTS: APH was 5.75 fold increased among cases (P=0.0001). LBW was more prevalent among babies born to the mothers with pregnancies complicated with first trimester vaginal bleeding (P=0.0001).CONCLUSIONS: Threatened miscarriage should be considered as high risk pregnancy requiring frequent antenatal visits and timely referral to higher centres when complications are identified.